2009
DOI: 10.1016/j.ydbio.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

RBP-J promotes neuronal differentiation and inhibits oligodendroglial development in adult neurogenesis

Abstract: Neurogenesis persists in restricted regions of the adult vertebrate brain. However, the molecular mechanisms supporting adult neurogenesis are not fully understood. Here we demonstrated that C cell-specific deletion of RBP-J in the adult subventricular zones (SVZs) caused reduction in numbers of mature granule cells in the olfactory bulbs (OBs) with concomitant increase in Olig2(+) oligodendroglial progenitors, although generation of immature neurons was enhanced in the SVZs. Adenovirus-mediated Cre introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…Collectively, Notch is unlikely an essential target of presenilin in mediating neuronal survival in the adult cerebral cortex. Consistent with this interpretation, RBP-J cKO mice, which were generated using independent ␣CaMKII-Cre lines, also failed to exhibit any phenotypes in excitatory neurons of the adult cerebral cortex, 4,5 although adult neurogenesis and glial cell fate specification in the subventricular zone was affected (74). This is consistent with data from our in situ hybridization analysis that showed Notch2 signals in the subventricular zone, the rostral migratory stream, and the olfactory bulb of the adult brain.…”
Section: Discussionsupporting
confidence: 86%
“…Collectively, Notch is unlikely an essential target of presenilin in mediating neuronal survival in the adult cerebral cortex. Consistent with this interpretation, RBP-J cKO mice, which were generated using independent ␣CaMKII-Cre lines, also failed to exhibit any phenotypes in excitatory neurons of the adult cerebral cortex, 4,5 although adult neurogenesis and glial cell fate specification in the subventricular zone was affected (74). This is consistent with data from our in situ hybridization analysis that showed Notch2 signals in the subventricular zone, the rostral migratory stream, and the olfactory bulb of the adult brain.…”
Section: Discussionsupporting
confidence: 86%
“…However, it was not clear whether only subsets or all neural stem cells are regulated by Notch signaling. It was also reported that when Rbpj is deleted in type C cells by using CaMKII-Cre driver, some oligodendrocyte precursors are formed at the expense of neurons, suggesting that Notch signaling is required for maturation of neurons (Fujimoto et al, 2009). However, the role for Notch signaling in adult neural stem cells remained to be analyzed.…”
Section: Requirement Of Notch Signaling For Maintenance Of Neural Stementioning
confidence: 98%
“…Thus, ablation of Notch1 from the targeted progenitor cells resulted in a persistent defect in neurogenesis, indicating the requirement of Notch1 for the continued production of neuroblasts and OB neurons. The Notch1 cKO phenotype was distinct to that caused by loss of RBP-J, the key transcriptional component of the Notch cascade, which resulted in an increase in neuroblasts in the SVZ and a burst of OB neuron formation (Carlén et al, 2009;Fujimoto et al, 2009;Imayoshi et al, 2010). (Giachino and Taylor, 2009).…”
Section: A Cell Autonomous Role For Notch1 In Adult Neurogenesismentioning
confidence: 99%
“…This implies that canonical Notch signaling through RBP-J is required for maintenance of qNSCs but that Notch1 is not. However, the effects of loss of RBP-J are in keeping with canonical Notch signaling playing multiple roles in adult neurogenesis, first suppressing proliferation and retaining NSCs in a quiescent state and secondly preventing differentiation of mitotic NSCs (Fujimoto et al, 2009;Imayoshi et al, 2010).…”
Section: Notch1 Regulates Homeostatic Neurogenesis In the Adult Forebmentioning
confidence: 99%